Sosialisasi Gemar Menabung Sejak Dini pada Siswa Kelas VII SMP Negeri 8 Ambon - Gloria A. D. Rante; Jossep Titirloloby; Gloria Sitaniapessy; Laury M. Ch. Huwae; Angela Ruban; Gratia D. Manuputty (Fakultas Teknik Universitas Cenderawasih, 2023)
Consumerism has become a problem in many communities nowadays, especially among teenagers. Growing a culture of saving from an early stage can solve this problem. Therefore, socialization with students about the importance of a culture of saving from an early age is essential to shape their behaviour to be more frugal and teach them to manage their finances. The socialization aims to educate students on the importance of saving early on and motivate them to set aside part of their income for savings. The result of the socialization is to grow students' enthusiasm for saving and increase knowledge about saving, such as the definition, the benefits, and the methods; it is highly expected that the seventh-grade students of SMP Negeri 8 Ambon can implement the saving habit in their lives.